ANALISIS MORFOMETRIK DAN POLA PERTUMBUHAN IKAN JUARO (Pangasius polyuranodon) DI PERAIRAN SUNGAI KAMPAR DAN SUNGAI SIAK PROVINSI RIAU - Lauura Hermala Yunita; Windarti .; Muhammad Fauzi (Jurnal Ruaya : Jurnal Penelitian dan Kajian Ilmu Perikanan dan Kelautan, 2020)
Pangasius polyuranodon commonly inhabit rivers in Riau such as Kampar and Siak Rivers. Evironmental condition of those rivers, however, are different. The Siak River has bad water quality, while that of the Kampar River is better and thus affects the morphological characteristic of the fish in general. To understand the morphological charateristic of fish from both rivers, a study has been conducted in March – June 2019. Fish was sampling once and they were analyzed in the laboratory. Results shown that general characteristics of the fish from both sampling areas are similar. The length-weight relationship, however, shoun that fish from the Siak River was smaller than that of the Kampar River. There was 170 – 360 mm TL, 41 – 474 gr BW and b value was 3,00 (isometric) for the fish of the Kampar River and there was 160 - 290 mm TL, 23 – 100 gr BW and b value was 1,83 (negative allometric). Secondary sexual characteristic of the fish from the Kampar River occured at around 250 mm TL, while that of the Siak River was 190 mm TL. Based on data obtained it can be concluded fish from the Kampar River growing faster than fish from the Siak River.